2017
DOI: 10.5217/ir.2017.15.4.495
|View full text |Cite
|
Sign up to set email alerts
|

Is methylation analysis ofSFRP2,TFPI2,NDRG4, andBMP3promoters suitable for colorectal cancer screening in the Korean population?

Abstract: Background/Aims Colorectal cancer (CRC) screening using stool DNA was recently found to yield good detection rates. A multi-target stool DNA test (Cologuard®, Exact Sciences), including methylated genes has been recently approved by the U.S. Food and Drug Administration. The aim of this study was to validate these aberrantly methylated genes as stool-based DNA markers for detecting CRC and colorectal advanced adenoma (AA) in the Korean population. Methods A single-cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 24 publications
(33 reference statements)
0
24
0
Order By: Relevance
“…, and WIF1, have been analyzed for the diagnosis of CRC. [82][83][84][85] To date, the United States Food and Drug Administration has approved only the Cologuard test (multitarget stool DNA test for CRC) for CRC screening. Compared to the gFOBT, the Cologuard test shows better sensitivity (13% vs. 52%) for detecting CRC.…”
Section: Crbp1 Cxcl21 Esr1 Gata4 Gstp1 Hltf Id4 Irf8 Itga4 Kmentioning
confidence: 99%
“…, and WIF1, have been analyzed for the diagnosis of CRC. [82][83][84][85] To date, the United States Food and Drug Administration has approved only the Cologuard test (multitarget stool DNA test for CRC) for CRC screening. Compared to the gFOBT, the Cologuard test shows better sensitivity (13% vs. 52%) for detecting CRC.…”
Section: Crbp1 Cxcl21 Esr1 Gata4 Gstp1 Hltf Id4 Irf8 Itga4 Kmentioning
confidence: 99%
“…A recent study of stool DNA methylation in an Asian population, assessing the methylation of SFRP2 , TFPI2 , NDRG4 , and BMP3 promoters, showed high sensitivities of 94.3% and 72.2% to detect both CRC and advanced adenoma, respectively, but with a low specificity of 55.0%. 4 A new blood screening test that examines methylated SEPT9 (Epi proColon ® ; Epigenomics AG, Berlin, Germany) was approved by the FDA in 2016. However, a large multicenter prospective study showed low sensitivities of 48.2% and 11.2% for detecting CRC and advanced adenoma, respectively with 91.5% specificity.…”
mentioning
confidence: 99%
“…In addition to the accurate detection for advanced-stage cancer, an ideal screening method should be able to effectively identify early-stage cancer and precursor lesions and thus reduce the subsequent risk of invasive disease. Previous studies have reported the diagnostic accuracy of the stool DNA methylation test for detecting precursor lesions, such as advanced adenoma and sessile serrated polyps, were lower than CRC [47,53,57,58]. The sensitivity of the stool DNA test for the detection of advanced precancerous lesions was around 42%-57% [32], approximately half of the detection sensitivity for CRC.…”
Section: Discussionmentioning
confidence: 93%